Respon Perkecambahan Benih Kemiri Sunan (Reutealis Trisperma) Terhadap Skarifikasi Kimia Dengan Asam Sulfat (H2so4) Pada Berbagai Lama Waktu Perendaman - Ismail, Ahmad Deni; Duryat, Duryat (Universitas Jambi, 2018)
The duration of submersion and the level of acid concentration which are the decisive factors to succed the chemical scarification. The duration of submersion should be adjusted to the level of seed skin thickness, the level of acid concentration and the type of acid used. This study aimed to analyze the inmersion effect of kemiri sunan seeds in sulfuric acid solution to break the seed dormancy and to get the most effective time of submersion in order to break the dormancy of kemiri sunan seed. The experiment was conducted in the greenhouse for 2 months (62 days). The randomized complete design was employed as experimental method. There were 4 treament tested, i.e : (1) control (without immersion in H2SO4 solution); (2) immersion in H2SO4 solution for 10 minutes; (3) immersion in H2SO4 solution for 20 minutes and (4) immersion in H2SO4 solution for 30 minutes. The results of research showed that control gave the best results in term of the percentage of germination (G), mean daily gremination (MDG), and germination rate (GR).